Food democracy as radical political agroecology: securing autonomy (alterity) by subverting the state-capital nexus - Tilzey, Mark (Frontiers in Sustainable Food Systems, 2024)
Food democracy and political agroecology, as closely allied social movements, have become associated in the main with what may be termed ‘agrarian populist’ and postcolonial problematics. While certainly ‘radical’ in relation to hegemonic neoliberal, or sub-hegemonic ‘national developmentalist’, framings of contemporary agricultural and ecological crises and their mitigatory responses to them, populist food democracy and political agroecology, it is argued here, fail convincingly to identify causality underlying the ‘political’ causes of these capitalogenic contradictions. While more convincing in identifying such causality in the ‘ecological’ domain in terms of the need to ‘localize’ and ‘re-territorialize’ food production and consumption networks, in its ‘political’ aspect populist food democracy and political agroecology demonstrate a failure to specify key ontological drivers of capitalogenic contradiction in terms of state, capital, class, and, more generally, power relations in their historical particularity. These shortcomings of ‘populist’ food democracy and agroecology in their ‘political’ aspect are exemplified by reference to key academic texts arising from the movement. The paper then proceeds to identify how these populist assumptions differ from a Marxian derived understanding of contradiction and the resulting proposal for a ‘radical’ political agroecology as substantive food democracy.